2013
DOI: 10.1159/000353804
|View full text |Cite
|
Sign up to set email alerts
|

Crush Cytology of a Primary Intraspinal Rhabdoid Papillary Meningioma: A Case Report

Abstract: Background: Both rhabdoid and papillary meningioma are rare variants of meningioma categorized as WHO grade III. Here, we report a rare case of combined rhabdoid papillary meningioma with discussion of its differential intraoperative cytologic diagnoses. Case: The patient was a 72-year-old female who presented with a huge mass at the cervical spine on MRI. The crush smears showed a radially arranged pattern of elongated tumor cells centered around the vessels, which formed a pseudorosette-like papillary struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Low-grade chondrosarcoma should be distinguished from chordoid meningioma, especially when showing frequent nuclear inclusions or grooves as in the present case [15,16,17]. Nuclear inclusions are commonly found in meningioma or ependymoma in intraoperative cytologic smears [1,18,19]. Epithelioid cells having partly vacuolar changes and a myxomucinous gelatinous background are shared features [20].…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade chondrosarcoma should be distinguished from chordoid meningioma, especially when showing frequent nuclear inclusions or grooves as in the present case [15,16,17]. Nuclear inclusions are commonly found in meningioma or ependymoma in intraoperative cytologic smears [1,18,19]. Epithelioid cells having partly vacuolar changes and a myxomucinous gelatinous background are shared features [20].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of resection is regarded as the important prognostic factor in papillary meningioma. Gross total resection results in less recurrence and mortality . Postoperative radiotherapy is associated with improved survival in papillary meningioma .…”
Section: Discussionmentioning
confidence: 99%
“…It is seen most frequently in the supratentorial compartment with cerebral convexities and parasagital region being the most preferred sites . Histopathologic features of papillary meningioma are well described, but cytological features are rarely been described …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Jeong et al . [ 13 ] have reported a case of primary intraspinal rhabdoid papillary meningioma with primary manifestation in the spinal cord of a 72-year-old female. They concluded that search for eosinophilic hyaline cytoplasm, rather than a fibrillary one, is critical for distinguishing it from other commonly encountered spinal cord tumors in the total absence of meningothelial whorls.…”
Section: Discussionmentioning
confidence: 99%